Studi Kasus: Pemberian Latihan Keseimbangan Dan Penguatan Otot Pada Penderita Diabetic Peripheral Neuropathy DM Tipe 2 - Muhammad Fakhrul Fauzi (Journal of Health and Therapy, 2021)
Diabetes mellitus is a heterogeneous metabolic disease characterized by hyperglycemia as a result of defects in insulin secretion, insulin action or both. Long-term diabetes comes with various complications including neuropathy. Diabetic Peripheral Neuropathy (DPN) is also known as nerve fiber injury that results in changes in motor, sensory, and proprioceptive functions. DPN also has lower extremity muscle weakness, decreased balance, coordination, gait control, and an increased risk of falling. This study aims to determine the effect of balance and muscle strengthening exercises in the lower extremities to reduce the risk of falling in diabetic peripheral neuropathy type 2 DM patients. SM is 65 years old, Christian, works as a housewife. After carrying out a physiotherapy program given for 3 meetings with balance training interventions, it has not been able to improve balance, but is able to increase muscle strength in diabetic peripheral diabetic patients with type 2 DM neuropathy.